EFFECT OF IRRIGATION INTERVALS AND FOLIAR OF SALICYLIC ACID ON GROWTH AND YIELD OF POTATO - & et al., AL-Jeboo (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiment was carried out in one of the private field in AL-Radwaniah westeren south of Baghdad to study the effect of irrigation intervals, irrigation after 6, 8 and 10 days (D1, D2 and D3) and irrigation of salicylic acid concentration (0, 50, 100, and 150 mg/l) (S0, S1, S2 and S3) on some vegetative growth and yield parameters. Potato tuber were planted on 1 Feb 2015 using application N, P, K in the rate 120: 60: 200 kg/ ha. Plants were irrigated after 6,8 and 10 days and spraying of salicylic acid three time, First in vegetative growth stage and in stolon intiation stage and in tuber intiation stage. Factorial experiment in Nisted design with three replication was used. Results showed that using 10 days as irrigation period (D3) significantly decreased vegetative growth and yield parameters compared to D1. Salicylic acid significantly increased in same characteristics. Interaction treatments showed D1S2 and D1S1 significantly increased wich gave highest plant length (91.70 and 90.30 cm) respectively and greatest leaf area (72.63 and 69.87 dsm2/plant) and gave highest yield per plant (1093 and 1069 g/plant) and highest total yield (58.25 and 56.98 ton/ha-1) respectively. The suggestion could be made that spraying of salicylic acid 50 mg/L three times with Irrigation duration 6 days resulted in highest yield per plant and highest total yield.